Effect of the preweaning nutritional state on the cardiac protein profile and functional performance of the rat heart - Pelouch, V; Kolár, F; Milerová, M; Ostádal, B (Molecular and cellular biochemistry, 1997)
The aim of the study was to find out whether the changes in nutritional status induced by different litter size during early postnatal development can influence quantitative and qualitative protein remodeling and contractile performance of the myocardium. Male Wistar rats born at the same day were pooled together at 2 days postbirth and assigned by random selection to dams in groups of 4, 8 or 16 rats/litter. The animals were investigated at the age of 4 and 16 weeks. The results revealed that the early postnatal nutritional modification altered weight parameters: whereas lower heart weight persisted in slow-growing rats until 16 weeks, higher body weight of fast-growing rats returned to the control level at the age of 16 weeks. Altered nutritional status influenced also protein remodeling of the myocardium: the concentration of all noncollagenous proteins (fractions of metabolic and contractile proteins) significantly increased in slow-growing rats, on the other hand, the concentration of collagenous proteins (pepsin-soluble and -insoluble fractions) was higher in fast-growing animals. The changes were, however, only transitional: three months after the end of the weaning period most protein changes returned to the control level. However, higher concentration of total blood lipids and triglycerides in fast-growing rats persisted until adulthood. Nutritional changes had, however, only minor effect on ventricular performance. No differences among groups were observed in basal values of the left ventricular pressure, while the maximum pressure attained after an acute ventricular loading and the contractile reserve were significantly decreased in slow-growing 4 week old rats. The functional consequence of altered nutritional status during weaning was only transitional, in agreement with the transient character of most structural and biochemical markers of myocardial remodeling.
Keywords: nutriční stav; velikost orgánu; Animal Nutritional Physiological Phenomena; proteiny; fyziologie výživy zvířat; Ventricular Function, Left; Male; funkce levé komory srdeční; Rats, Wistar; Organ Size; srdce; krevní glukóza; Myocardium; mužské pohlaví; potkani Wistar; Body Weight; krysa rodu Rattus; Myocardial Contraction; Animals, Suckling; funkční vyšetření srdce; Animals; zvířata; Rats; Nutritional Status; kojená zvířata; kontrakce myokardu; Weaning; Heart Function Tests; Heart; Blood Glucose; Proteins; tělesná hmotnost; odstavení; myokard